Clinical Implications of Ketosis in Children with Benign Convulsions with Mild Gastroenteritis - Lee, Jeong-Yong (J Clin Neurol, 2020)
BACKGROUND AND PURPOSE: The pathophysiologic mechanisms underlying benign convulsions with mild gastroenteritis (CwG) in children remain unclear. We investigated the incidence of ketosis in CwG and whether this is related to seizures. METHODS: This retrospective study included children aged from 6 months to 6 years who visited our emergency department and were diagnosed as CwG between June 2015 and December 2018. The clinical and laboratory data were analyzed for these cases. Ketosis and severe ketosis were defined as blood β-hydroxybutyrate levels of ≥0.6 and ≥4.5 mmol/L, respectively. RESULTS: We enrolled 42 pediatric CwG patients aged 21.0±11.5 months (mean±SD) whose blood β-hydroxybutyrate level was 3.65±1.51 mmol/L. Ketosis was observed in 95.2% of these children, while 35.7% had severe ketosis. Compared to the non-severe-ketosis group (n=27), the severe-ketosis group (n=15) demonstrated significantly lower blood glucose levels (68.8 vs. 82.6 mg/dL, p=0.020) and sodium levels (134.2 vs. 135.6 mEq/L, p=0.018), and included a larger proportion of low-body-weight children (defined as adjusted weight <50th percentile for age and sex) (53.3% vs. 18.5%, p=0.019). However, the incidence of repetitive seizures (two or more during an illness period) did not differ between these groups. Moreover, severe ketosis was not associated with the risk of seizure recurrence in the emergency department. CONCLUSIONS: Children with CwG are in a state of considerable ketosis. Severe ketosis in CwG may be associated with low blood glucose and sodium levels but does not reduce seizure recurrence.